Exploring the attitudes and practices among student clinicians in India on multilingual issues in the field of speech-language pathology - Indira Valliappan; Roha Kaipa; Sudhin Karuppali (CoDAS, 2023)
ABSTRACT Purpose Student clinicians (graduates and undergraduates) in speech-language pathology deal with various multilingual issues while providing clinical services to individuals with language impairments. This study explores the attitudes and practices of undergraduate and graduate speech-language pathology students in India towards multilingualism and handling these issues. Methods One hundred and twenty-eight students (71 graduates and 57 undergraduates) participated in the study. Phase 1 of the study included the development of a questionnaire to explore the attitudes and practices of student clinicians in speech-language pathology. The questionnaire was converted into an online survey in Phase 2. Phase 3 comprised data and statistical analysis to summarize and interpret collected data. Results Graduate and undergraduate students significantly differed in their attitudes and perception toward multilingual issues (p<0.05). Most clinicians demanded a change in the current views on assessment/intervention, considering the linguistic background of the patient/caregivers. Other issues surrounding multilingualism included parents' education levels, lack of sufficient assessment tools, unavailability of translators/interpreters, and poor linguistic competency of clinicians. Conclusion These findings assist academic programs in planning and developing modules to aid students in handling the major multilingual issues encountered during clinical interactions.